The coupling coordination relationship and obstacle factors of public cultural services and economic development: A case study of 31 regions in China - Bingtao Xu; Zongye Gu; Ziwen Wang; Yaqiao Chen; Yanling Wang (PLoS ONE, 2026)
The interrelationship between public cultural services (PCSs) and economic development (ED) has emerged as an important theme in academic inquiry, playing a pivotal role in advancing global sustainability. This research treats PCSs and ED as distinct systems to investigate pathways for achieving optimal coordination and balanced progress. By constructing a comprehensive evaluation framework for PCS-ED interactions, this work utilizes analytical approaches including coupled coordination measurement, kernel density analysis, spatial Markov modeling, and obstacle factor assessment to analyze their coordinated development among 31 provincial regions in China from 2014 to 2023. Our findings reveal notable geographical disparities, characterized by a pronounced positive spatial autocorrelation in coordination levels between PCS and ED. The degree of coupling coordination is higher in the eastern coastal regions, whereas that in the western and northeastern provinces exhibit lower levels of coordination. The primary impediments to balanced development are attributed to deficiencies in library exhibitions and public lectures, and constraints imposed by fiscal revenue limitations. Our findings offer valuable empirical support for optimizing the distribution of public cultural assets and fostering equitable regional economic advancement. This study echoes the global initiative of the United Nations Educational, Scientific and Cultural Organization (UNESCO) on culture for sustainable development.